Forest management practices from islamic perspective (2016)
Today, the world is facing the problem of global warming and other environmental crises and malaises; and the effect of these phenomena has serious implications on the survival of man. Many researchers have looked at the problem from different perspectives with a view to finding sustainable solutions. Not much attention has been given by both Muslims and non-Muslims to the Islamic directives on forest management, one of the ways by which the global warming and other environmental crises can be abated. It is against this backdrop that the paper aims at examining the Islamic directives on forest management. A descriptive approach and textual analysis of the Qur’an and the Sunnah were adopted in carrying out this research. The study finds that taking care of the environment is tantamount to good deeds, and as good as other acts stated in the Qur’an and the Sunnah. It shows the honour given to trees and environment. The paper presents how trees mop-up carbon dioxide, a green house gas, from the atmosphere and replenish the oxygen content to give man clean air; fix atmospheric nitrogen to rejuvenate the soil; reduce use of inorganic nitrogen fertilizer and emission of nitrous oxide (N2O). It is against Islamic teachings to cut trees or abuse forests without genuine reason. Therefore, adoption of the teachings of Islam in the areas of forest management can go a long way in changing peoples’ attitude positively towards its use and sustainability.